Costus Root Extract Preserves Thyroid Hormones Levels, Thyroglobulin Expression and Thyroid Tissues in Rats Receiving Valproate Sodium - Marwa Salah Mahmoud (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Valproate sodium is an anticonvulsant drug. Saussurea lappa (costus) is a medicinal plant rich with antioxidants. This research aimed to assess the protective effect of costus root extract against valproate sodium-induced thyrotoxicity.METHODS: Eighty adult male albino rats were equally divided into four groups; group I: untreated control, group II: rats were given 200 mg/kg BW valproate sodium orally and daily for 8 weeks, group III: rats were given 300 mg/kg BW costus root extract orally and daily for 8 weeks, and group IV: rats were given combination of valproate sodium and costus root extract. After 8 weeks, blood samples were collected to evaluate T3, T4 and thyroid-stimulating hormone (TSH) levels. Thyroid gland samples were handled for light and electron microscopic investigation. The heights of follicular cells, area % of collagen fibers and color intensity of thyroglobulin immunoreaction were statistically analyzed. RESULTS: After being given valproate sodium as an induction, hormonal assay showed significant decrease in serum T3 and T4 and significant increase of TSH. Follicular and cellular alterations were shown by light and electron microscopes. Morphometric study revealed increased follicular cell height and area % of collagen fibers and decreased color intensity of thyroglobulin. In contrast, costus root extract appeared to have a protective role against valproate sodium-induced thyroid injury. Most of the changes induced by valproate sodium were not observed after supplementation with the plant root extract.CONCLUSION: Valproate sodium has serious effects on the function and structure of thyroid gland, and this study shows that costus root extract could have a protective effect against these effects.KEYWORDS: valproate sodium, rat, thyrotoxicity, Saussurea lappa